Superparamagnetic Iron Oxide Nanoparticles - Lüdtke-Buzug Kerstin; Penxová Zuzana (Current Directions in Biomedical Engineering, 2019)
The direct detection of the spatial distribution of Superparamagnetic Iron Oxide Nanoparticles (SPIONs) as a tracer for Magnetic Particle Imaging (MPI) enables threedimensional functional images with high spatial and temporal resolution. The commercially available tracers have not been developed primarily for MPI. Therefore, they do not sufficiently contribute to the desired image quality. Hence, optimizing the SPIONs during the production process is of interest. A peculiarity of the here presented synthesis method - the alkaline coprecipitation - is that this process takes place under ultrasonic control. The use of ultrasound creates extraordinary reaction conditions through sonochemical phenomena, such as formation, growth and implosive collapse of cavitation bubbles within a liquid. In addition, the ultrasonic waves and the oscillation of the medium improve the mixing process and thus ensure the homogenization during the synthesis. The objective of this study is the variation of ultrasonic frequencies and the type of used dextran as coating material, to provide SPIONs with better performance for MPI and more suitable properties for in vivo application. The focus of the optimization is to increase the magnetite core size while simultaneously reducing the hydrodynamic size. The experiments have shown that both, the ultrasound frequency and the molecular weight of used dextran, influence the properties of the SPIONs.